Comparative Analysis of Different Body Composition, Mucus Biochemical Indices, and Body Color in Five Strains of Larimichthys crocea - Hongjin Deng; Quanyou Guo; Banghong Wei; Jiehui Zhong; Mengyao Zheng; Yao Zheng; Na Lin; Shengyang Zheng (Fishes)
The large yellow croaker, or Larimichthys crocea, is highly prized for its golden color and nutritional content. The purpose of this study was to investigate the differences in body composition, mucus biochemical indices and body color in five strains of large yellow croakers (body weight: 347.01 ± 5.86 g). To conduct genetic diversity analyses of the populations, a total of 50 tailfin samples were randomly chosen from the following populations of large yellow croakers: wild (LYC1), Dai-qu population (LYC2), Yongdai 1 (LYC3), Min-yuedong population (LYC4), and Fufa 1 (LYC5). The findings demonstrated that the LYC3 group’s pigment contents, crude protein, crude lipid, and chromatic values were comparable to those of the LYC1 group (p > 0.05). There was no significant difference between the LYC1 and LYC5 groups’ mucus superoxide dismutase (SOD) and catalase (CAT) activities (p > 0.05). The alkaline phosphatases (ALP), acid phosphatases (ACP), and lysozyme (LYS) activities of the mucus in the LYC1 group were not significantly different from the LYC3 group (p > 0.05). The back skin mRNA expressions of tyrosinase (tyr), tyrosinase-related protein 1 (tyrp1), dopachrome tautomerase (dct), microphtalmia-associated transcription factor (mitf), and melanocortin 1 receptor (mc1r) were significantly up-regulated in the LYC2 and LYC4 groups compared to the LYC1, LYC3, and LYC5 groups (p < 0.05). Forkhead box d3 (foxd3), paired box 3 (pax3), purine nucleoside phosphorylase 4a (pnp4a), aristaless-like homeobox 4a (alx4a), cAMP dependent protein kinase (pka), anaplastic lymphoma kinase (alk), leukocyte receptor tyrosine kinase (ltk), and colony stimulating factor (fms) were among the mRNA expressions of the abdominal skin in the LYC1, LYC3, and LYC5 groups significantly higher than those in the LYC2 and LYC4 groups (p < 0.05). In conclusion, the LYC3 group’s crude protein, crude lipid, carotenoid, and lutein contents were most similar to those of the large yellow croaker found in the wild. Furthermore, the molecular mechanism underlying the variations in body color among the various strains of large yellow croakers was supplied for additional research.